О решении задачи целочисленной оптимизации на выпуклых множествах в условиях неопределенности данных - Семенова, Н.В. (Теорія оптимальних рішень, 2005)
The paper constructs and substantiates decomposition methods used to solve problems exactly and approximately. Such problems emerge when one investigates complicated integer optimization models with controllable and inexact data. Methods are based on approximation of initial problems by problems of a simpler structure, unite and use the ideas of relaxation, linearization and the Kelley cutting plane methods.